CPC-104 Pharmacists and Clinical Trials: Perspectives and Results at the Medical Oncology Operations Unit of the G. Rummo Hospital, Benevento. (12th March 2013) - Melillo, A; Ruggiero, F; Russo, L
Abstract : Background: The rules on Controlled Clinical Trials require the expertise of a pharmacist specialising in internal monitoring of ongoing trials in the Operations Unit. Purpose: To highlight the role of the pharmacist dedicated to research projects, who sees that trials are conducted in accordance with GCP and in compliance with applicable regulations. Materials and Methods: From January 2010 the pharmacy has created a database to monitor all studies approved by the Ethics Committee, both observational and experimental. Having a dedicated pharmacist has led to: proper storage of drugs, completing the application form accompanying the samples, storage of electronic and paper documentation of the experimental samples, fitting directly in Pharmacy, randomization of patients enrolled and completing the Drug Accountability. Results: 40 clinical trials have been conducted, 26 of which were conducted in the Oncology OU, 3 in Pulmonary and 8 in Cardiology, 1 in Rheumatology, 2 in Dermatology. As regards the preparation of the antiblastic treatments, the treatment setting provided by the experimental protocols accounted for 5% of all cancer preparations performed in the pharmacy. 83% of the studies (33 studies) were for profit, non-profit research accounted for only 17% of the studies. In 2012 the number of for-profit studies increased compared to 2010; we hope these will be particularly useful to point out any problems of current clinical practise. Conclusions: The dedicated pharmacist can ensure that research is conducted properly, both the management of experimental drugs and collaboration with the clinical evaluations related to routes of administration, any incompatibilities, monitoring of side effects and/or adverse events, interactions with associated therapies. In conclusion it is evident that the multidisciplinary approach and sharing of expertise with the medical and nursing staff encourages adherence to protocols. No conflict of interest.